Perancangan Animasi 2D “Mentilin Si Tarsius Mungil” sebagai Upaya Pelestarian dan Edukasi Masyarakat di Pulau Bangka - Widya Puspita Sari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Animated films are not only a medium of entertainment but also an effective tool for delivering moral, social, and educational values through innovative storytelling and engaging visual styles. In Indonesia, although many animated films are broadcast on national television, only a limited number originate from domestic creators. This condition highlights the need to strengthen local creative content that reflects Indonesia’s cultural and environmental identity. The present design project aims to develop an alternative television program in the form of a 2D animated film that emphasizes the preservation of Mentilin, an endemic animal of Bangka Island, while simultaneously serving as an educational medium for the local community. The research and design process employed a qualitative approach, focusing on data collection through observation, interviews, and literature review to identify effective strategies for socialization and education. The animation production of Mentilin, The Tiny Tarsier was carried out in three main stages: pre-production, including concept development and storyboarding; production, involving character design, background creation, and animation; and post-production, which covered editing, sound design, and final rendering. The preliminary evaluation indicated that the animation successfully captured local cultural elements and delivered messages about environmental awareness in an engaging manner. This design is expected not only to provide a creative educational platform for the community but also to contribute to the broader efforts of environmental preservation and the development of Indonesia’s animation industry. Furthermore, the program has the potential to be expanded as a replicable model for other regions in promoting endemic species conservation through creative media.